Plasmid construction via in vivo cloning for the search and characterization of iron-binding oligopeptides in Saccharomyces cerevisiae - Canales , Pamela E. (2024)
Saccharomyces cerevisiae yeast serves as a nutritional supplement and food additive that may offer highly bioavailable iron. Several studies have demonstrated the viability of using iron-chelating oligopeptides to treat anaemia, suggesting that their production in yeast cells could advantageously provide an easy-to-use supplement. In this study, an in vivo cloning strategy was optimized to construct a semi-random plasmid library that enables the production of oligopeptides with six repetitions of Asp/Glu-Asp/Glu-Leu sequences. In these sequences, the first and second positions can include either aspartate or glutamate residues, while the third is always leucine. Additionally, several plasmids were constructed to allow the study of variants of the Arg-Glu-Glu oligopeptide, previously reported as an iron chelator. In each case, the required plasmid constructions were performed using an in vivo cloning strategy in S. cerevisiae, based on gap repair by homologous recombination. The procedure involves the co-transformation of yeast cells with the linearized plasmid and the fragment to be cloned, both with homologous flanking sequences. The resulting transformants harbor the correctly assembled plasmids and begin expressing the cloned genes, thereby enabling immediate analysis of the synthesized oligopeptides with known or semi-random sequences.